Crypto Art and NFT - Doğan, Betül; ERSÖZ, Sare Şeyma; Şahin, Cengiz (Journal of History Culture and Art Research, 2022)
With the advancement of new media technologies, digital art has become a concept that we often hear in every aspect of our lives. Traditional artists started to reshape visual arts by developing new perspectives. With the concepts of blockchain and NFT (Non-Fungible Token), which are included in the art life, the understanding of crypto art has emerged. Crypto art is based on the idea of buying and selling digitally produced artworks like physical artworks. NFT is an indicator of the authenticity, transparency and unalterability of digital work. With NFTs, which have a high degree of confidentiality and transparency, artists have started to deliver their works not through intermediaries such as galleries or auctions but directly to art lovers in a very short time. This study is a qualitative research based on a descriptive narrative about crypto art, NFT and digital art and design based on them. Crypto art, blockchain and NFT concepts are discussed as a whole and the relationship between them is mentioned. An extensive literature review was conducted to determine the conceptual framework of the study. While the research is about the development of crypto art from its beginning to today’s applications, it is exemplified by the works of local and foreign artists in this context. In the last session of the study, the different perspectives that the understanding of crypto art brought to art, the differences between traditional art and the positive and negative aspects of crypto art were evaluated. It is foreseen that this understanding of art can be carried further, especially with the acceptance of the new generation and the advancement of technology.